PENGARUH PENAMBAHAN ABU LIMBAH PEMOTONGAN KAYU SEBAGAI PENGGANTI FILLER TERHADAP KARAKTERISTIK MARSHALL PADA CAMPURAN ASPHALT CONCRETE-BINDER COURSE (AC-BC) - Vella Anggreana; Dino Hardian (Akselerasi : Jurnal Ilmiah Teknik Sipil, 2024)
Most filler materials are natural products such as stone ash which is increasingly limited in quantity and has a high economic value. For this reason, it is necessary to innovate by using alternative replacement materials in the form of waste such as sawdust in an effort to obtain a more economical replacement material and the amount in the field is still large. The purpose of this study was to determine the effect of using wood cutting waste ash filler in AC-BC mixture. This research was conducted using the 2018 Bina Marga Specifications and using the Marshall Test method. The percentage of wood cutting waste ash used was 0%, 10%, 20%, 30%, and 40%. Based on the research results, the optimum asphalt content is 5.8%. The greater the mixture of wood cutting waste ash filler composition, the lower the VMA and VIM values, while the higher the VFA value. The VMA, VFA and Stability values still meet the requirements of the 2018 Bina Marga Specifications. VIM and flow values increased and decreased in each variation of kulim wood ash mixed. For the stability value in the 0% and 10% variations of the culim wood ash mixture, it increased from 1815.261 - 1863.761Kg, but in the 20% - 40% variation it decreased from 1551.979 - 1281.768Kg but still met the requirements of the 2018 Bina Marga General Specifications. The flow value in the 0% and 10% variations increased from 3.20 - 3.87mm, but the 20% - 40% variation also experienced an increase that exceeded the maximum limit of the 2018 Bina Marga Specifications from 4.03 - 4.70mm. In all of the kulim wood ash filler compositions used, only the 0% and 10% variations of kulim wood ash met the requirements of the 2018 Bina Marga General Specifications. Meanwhile, the maximum composition of the culim wood ash filler mixture was obtained in the 10% culim wood ash variation with a VMA value of 16.995%, VIM of 3.891%, VFA of 77.102%, Stability of 1863.761 Kg and Flow of 3.87 mm.